2005
DOI: 10.1158/0008-5472.can-05-2300
|View full text |Cite
|
Sign up to set email alerts
|

Automated Quantitative Analysis of Activator Protein-2α Subcellular Expression in Melanoma Tissue Microarrays Correlates with Survival Prediction

Abstract: The activator protein-2A (AP-2) transcription factor plays a key role in regulating expression of genes involved in tumor growth and metastasis of human melanoma. We sought to assess the prognostic significance of AP-2 expression and its role in the transition of nevi to metastatic melanoma. Two cohorts were analyzed. One was a ''progression'' microarray containing melanoma specimens from M.D. Anderson Cancer Center representing 84 cases and the other was a retrospective cohort from Yale University representin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
38
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 63 publications
(42 citation statements)
references
References 23 publications
4
38
0
Order By: Relevance
“…Quantitative analysis of a large retrospective cohort of patients suffering from melanoma reveals that a high cytoplasmic-to-nuclear ratio of AP2␣ correlates with a poor prognosis. In addition, a loss of AP2␣ expression has been associated with malignant transformation and melanoma progression (34,51). Also, a recent in vitro study demonstrated that AP2␣ transcription factor overexpression could reduce cell invasion (52).…”
Section: Discussionmentioning
confidence: 99%
“…Quantitative analysis of a large retrospective cohort of patients suffering from melanoma reveals that a high cytoplasmic-to-nuclear ratio of AP2␣ correlates with a poor prognosis. In addition, a loss of AP2␣ expression has been associated with malignant transformation and melanoma progression (34,51). Also, a recent in vitro study demonstrated that AP2␣ transcription factor overexpression could reduce cell invasion (52).…”
Section: Discussionmentioning
confidence: 99%
“…39 Reports by others have suggested that translocation of AP-2 from the cytoplasm to the nucleus is disrupted during melanoma progression and is a crucial event in the development of melanoma. 40 AP-2 may act to regulate not only Bcl-2 expression but also several other genes whose products are involved in tumor growth and metastasis of melanoma. AP-2 proteins were reported to bind with p53 to p53 target genes such as p21 and so act as a tumor suppressor.…”
Section: Discussionmentioning
confidence: 99%
“…This method calculates marker expression on a continuous scale by using pixel intensity and is shown to be widely applicable for biomarker analysis. [8][9][10][11][12][13][14] Previous measurements of ER by AQUA have correlated well with IHC analysis on tissue from two large clinical trials and have also predicted response to tamoxifen. 15,16 In an attempt to both quantify and standardize the measurement of ER in patient tissue, we first sought to define an ER cut point with biologic and clinical relevance.…”
Section: Journal Of Clinical Oncology O R I G I N a L R E P O R T V Omentioning
confidence: 99%